Online-Based Learning Innovation in the Covid-19 Pandemic : (Study of PAUD Teacher Innovation during Covid 19 in Mataram City) - Ismail Ismail; Muhammad Muhammad; Bahtiar Bahtiar (Jurnal Ilmiah Profesi Pendidikan, 2022)
The Covid-19 pandemic caused fundamental changes in education. One of them is the learning process is done online. This makes teachers innovate in the online learning process so that the learning process can run well and smoothly. Thus, it cannot be denied that the Covid19 pandemic has brought about a change in a new paradigm shift for teachers towards online learning that is rich with innovation. This study aims to describe Online-Based Learning Innovations implemented by PAUD teachers during the Covid 19 Pandemic in Mataram City. This study uses a survey method with a qualitative approach. In this study, data were obtained from interviews with 6 teachers spread across 6 sub-districts in Mataram City. The sampling technique used is simple random sampling. Data collection techniques used in this study were interviews and documentation. Data analysis used the Miles and Huberman model, which consisted of data collection, data reduction, and data presentation. The results showed that the innovations carried out by PAUD teachers were Learning from Home, Online Learning Via Whatsapp Group, Home Visit, Offline Rolling System, Parenting Team Work, Sasak culture-based ecoprint learning, and project-based learning.